2003
DOI: 10.1002/da.10114
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of catechol-O-Methyltransferase Gene Polymorphism in Obsessive-Compulsive Disorder

Abstract: The COMT gene has been implicated to be involved in the pathogenesis of obsessive-compulsive disorder (OCD) and various other psychiatric disorders. COMT enzyme activity is governed by a common genetic polymorphism at codon 158 that results in substantial 3- to 4-fold variation in enzymatic activity [a high-activity COMT variant (H) and a low activity variant (L)]. This study evaluates the association between OCD and the COMT gene polymorphism. Fifty-nine OCD patients that were diagnosed according to DSM-IV cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 32 publications
1
25
0
2
Order By: Relevance
“…Schindler et al (2000) did not find an association between any particular allele and OCD, but found a tendency for an association with homozygosity at the COMT locus. Ohara et al (1998) did not find any association in a small sample of 24 Japanese patients and neither did Erdal et al (2003) in a sample of 59 Turkish patients. A recent meta-analysis of the COMT gene in 144 OCD patients and 337 controls showed insufficient evidence to support an association (Azzam et al, 2002).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Schindler et al (2000) did not find an association between any particular allele and OCD, but found a tendency for an association with homozygosity at the COMT locus. Ohara et al (1998) did not find any association in a small sample of 24 Japanese patients and neither did Erdal et al (2003) in a sample of 59 Turkish patients. A recent meta-analysis of the COMT gene in 144 OCD patients and 337 controls showed insufficient evidence to support an association (Azzam et al, 2002).…”
Section: Discussionmentioning
confidence: 68%
“…The GYA transition in codon 158 of the COMT gene results in a valine to methionine substitution and is associated with a three-to fourfold decrease in enzyme activity (valine = high-activity, methionine = low-activity) (Lotta et al, 1995). It has already been reported by Karayiourgou et al (1997) that the lowactivity COMT (COMT L) allele occurs significantly more frequently in male OCD patients, but opposing results have also been obtained (Erdal et al, 2003;Karayiorgou et al, 1999;Ohara et al, 1998). In addition, one might theorize that lower densities of the D 2 receptor in OCD patients are caused by genetic factors.…”
Section: Introductionmentioning
confidence: 98%
“…In one study, the COMT Val158Met genotype was associated with OCD [Niehaus et al, 2001]. Three studies showed no association between any of the COMT Val158-Met polymorphism genotypes or allele frequencies between cases and controls [Ohara et al, 1998;Erdal et al, 2003;Meira-Lima et al, 2004]. Four studies used a family-based approach.…”
Section: Introductionmentioning
confidence: 95%
“…[19][20][21][25][26][27][28] See Supplementary Information for details of the omitted studies. The individual included studies contained 17-155 OCD cases and 54-327 controls, totalling 606 subjects with OCD and 1302 controls (Table 1).…”
Section: Meta-analysismentioning
confidence: 99%